Immune status in infection by cytomegalovirus in women with bad obstetric history - Acharya, D; Shrestha, S; Bogati, B; Sherchan, JB; Karki, P; Yadav, A; Madhup, SK; Tuladhar, NR (International Journal of Infection and Microbiology, 2013)
Introduction: Viral infections during pregnancy carry a risk for intrauterine transmission which may result in fetal damage. Bad obstetric history implies for previous unfavorable foetal outcome in terms of two or more consecutive spontaneous abortions, history of intrauterine foetal death, intrauterine growth retardation, still birth, early neonatal death and congenital anomalies. Cytomegalovirus, a ubiquitous virus belonging to the herpes family, is known to cause abnormal fetal outcome. We aim to determine the possible involvement of CMV infection among pregnant women with bad obstetric history Materials and Methods: A cross sectional study was carried out among 136 women with bad obstetric outcome attending Dhulikhel Hospital- Kathmandu University Hospital. The cytomegalovirus specific IgG and IgM antibodies were determined by ELISA test. Data were analyzed using SPSS, version 17.0 and interpreted according to frequency distribution and percentage. The data was considered significant if the p-value was <0.05. Results: The results revealed that 87 (63.9%) out of 136 patients were positive for CMV IgG antibodies and only one (0.007%) patient was positive for CMV IgM. The majority of the patients were of the age between 20 and 29 years (99/136) and it was observed that most of the positive CMV IgG were participants of the same age group (63/ 99). There was no significant association of CMV seropositivity with the age of participants (p value 0.9). Conclusion: CMV infection could be the risk factor for BOH and may play a vital role in determining the foetal outcome. Thus we recommend routine serological testing to all pregnant women with or without BOH attending the antenatal clinics for both CMV specific IgG and IgM. DOI: http://doi.dx.org/10.3126/ijim.v2i1.7663 Int J Infect Microbiol 2013;2(1):3-6